Stories of stress: unveiling professional anxiety in mathematics teaching - Simkhada, Daya Ram; Dahal, Niroj; Pant, Binod Prasad; Luitel, Laxman; Manandhar, Netra Kumar (Frontiers in Education, 2025)
Professional anxiety in teaching refers to the stress and nervousness that educators experience due to their job duties and the challenges they encounter. This article explores the prevalence of professional anxiety among secondary school mathematics teachers at private schools in Nepal. The study aims to address the question: How do secondary school mathematics teachers narrate their experiences of professional anxiety? Using narrative inquiry as a research method and grounded on the theoretical perspective and lens of the job demand-control-support model (JDCS) and self-efficacy learning theory, this study narrates the stories of three secondary school mathematics teachers (two males and one female) from different private schools of Kathmandu Valley, Nepal. In-depth interviews were conducted for data collection, and identified and generated themes aligned to professional anxiety were used to analyze the findings. The findings reflect that professional anxiety increases over time. This research reveals that mathematics teachers, those in private schools, experience high levels of anxiety that persist over the years. Anxiety is linked to pressures such as the lack of a proper career plan, the gap between learning theories and actual classroom contexts, an inadequately structured curriculum, and insufficient resources for integrating technology into teaching practices. For boosting math teachers’ professional responsibilities, the study concluded that understanding the causes and impacts of professional anxiety in teaching is crucial for developing effective supportive strategies. This study is a valuable resource for mathematics teachers to reflect on their professional anxiety.